Sikap Yang Harus Dilakukan Masyarakat Ketika Bertemu Dengan Anak Berkebutuhan Khusus (ABK) - Ihsan Nugraha; Naudy Hanoem; Raisa Aqila; Yuliana Sagala; Siti Hamidah (Simpati, 2024)
This article was created to provide information about the right attitude and should be taken by the community when interacting with Persons with Special Needs. With so many types of people with special needs in society, such as the blind, deaf, mentally retarded, quadriplegic, and disabled, the treatment that can be done and provided by the general public should also be carried out differently by adjusting the constraints and needs needed by those with special n (Rosmawati, 2019) (Alim, 2019; Rahayu & Marheni, 2020; Suprapmanto, Nuralifa, Albela, & dkk, 2022; Purba, 2016; Dewi, 2019)eeds. As one of them is the CSOM technique which can be a guide not only for blind people, but also for the wider community when interacting with someone who has visual impairments. The adoption of this topic itself is based ons the experience that researchers have and experience when they are confused about what to behave, whether the person with special needs needs assistance, and if they do need assistance, what kind of assistance and how should be given when meeting with persons with special needs in public place. The research method used in this research itself is a quantitative survei method involving respondents to further strengthen the research that waswas made. The results of the research show that there are many things that can be found and done as an effort to increase the confidence of the general public to interact with Persons with Special Needs in their daily activities. The hope is that this research can dispel doubts that may arise and be experienced when we are going to help or interact with persons with special needs in the future in community activities and can provide information about what to do when interacting with persons with special needs.